2017
DOI: 10.7567/jjap.56.053001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lattice strain on cobalt ferrite Co0.75Fe2.25O4(111) thin films

Abstract: We report the optimum conditions for the epitaxial growth of CoxFe3−xO4 (CFO) (111) thin films with x = 0.75 on an α-Al2O3(0001) substrate via reactive RF magnetron sputtering. The lattice strain evaluated by X-ray diffraction measurements is as small as 0.11% in spite of the large lattice mismatch between CFO(111) and α-Al2O3(0001). The CFO(111) thin films grown under the optimal conditions exhibit magnetic anisotropy with the easy axis of magnetization perpendicular to the films. The induced uniaxial anisotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…23 However, there is a relatively large lattice mismatch between CFO (111) and Al 2 O 3 (0001). 24 LiTaO 3 is a multifunctional single crystal substrate material, and its crystal structure is similar to that of Al 2 O 3 . There is a smaller lattice mismatch and a larger difference in the thermal expansion coefficient between CFO and LiTaO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…23 However, there is a relatively large lattice mismatch between CFO (111) and Al 2 O 3 (0001). 24 LiTaO 3 is a multifunctional single crystal substrate material, and its crystal structure is similar to that of Al 2 O 3 . There is a smaller lattice mismatch and a larger difference in the thermal expansion coefficient between CFO and LiTaO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…3) In addition, it is reported that applying in-plane tensile stress causes tetragonal strain, thereby overcoming the shape magnetic anisotropy and showing an easy axis of magnetization perpendicular to the plane. [4][5][6][7][8][9][10][11] Investigation of magnetic anisotropy by the magnetoelastic effect has been conducted by preparing CFO thin films on various substrates to apply tetragonal strain. [7][8][9][10][11][12][13][14][15][16][17] Since the lattice constant of CFO is slightly smaller than twice the lattice constant of MgO, and a lattice mismatch occurs when epitaxially grown.…”
Section: Introductionmentioning
confidence: 99%